DEEP LEARNING IN ANIMAL CLASSIFICATION SYSTEM - V, Thenarasi; B N, Santhosh Kumar; Urs M, Prakasha Raje; Y H, Sharath Kumar; R, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this work, we propose a method for the classification of animal in images. Initially, a region merging segmentation method is used to perform segmentation in order to eliminate the background from the given image. From segmented animal images, the shape, texture and color features are extracted. Deep learning with Convolution Network and Support vector is considered for classification. To corroborate the efficacy of the proposed method, an experiment was conducted on our own data set of 30 classes of animals, which consisted of 600 sample images. The experiment was conducted by picking images randomly from the database to study the effect of classification accuracy, and the results show that the Deep Learning classifier achieves good performance.